Identification of a Serum Exosome-Derived lncRNA‒miRNA‒mRNA ceRNA Network in Patients with Endometriosis - Yan Huang; Deyu Zhang; Yingfang Zhou; Chao Peng (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: Endometriosis (EM), a gynecological disorder that is dependent on estrogen and causes inflammation, is prevalent among women of reproductive age and is considered a chronic condition. The involvement of noncoding RNAs in exosomes is crucial for the progression of EM. This study aimed to determine exosomal microRNA (miRNA) biomarkers in EM. Methods: Exosomes were isolated and characterized from the plasma of patients with EM and controls. Exosomal miRNA was sequenced using microarrays. EM-related differential miRNAs (DE-miRNAs) were identified using analysis of differential miRNA expression and weighted coexpression network analysis. The common pairs of long noncoding RNA (lncRNA)-miRNA and miRNA-mRNA were determined. Cytoscape was used to establish the regulatory network of characteristic genes known as competitive endogenous RNA (ceRNA), and the hub miRNAs, hub mRNAs, and hub lncRNAs were identified. Results: We isolated plasma exosomes from 10 control and 10 EM patients. We obtained a total of 50 DE-miRNAs, consisting of 7 miRNAs that were upregulated and 43 miRNAs that were downregulated. A network of ceRNA regulation was constructed using the diagnostic miRNAs, which revealed a total of 36 lncRNAs, 20 miRNAs, and 264 mRNAs associated with EM. Additionally, 10 lncRNAs (GAS5, MALAT1, FGD5-AS1, HCG18, SNHG16, XIST, OIP5-AS1, NEAT1, KCNQ1OT1, and SNHG12), 10 miRNAs (hsa-miR-361-5p, hsa-miR-19b-3p, hsa-let-7f-5p, hsa-miR-23a-3p, hsa-miR-199a-3p, hsa-miR-18a-5p, hsa-miR-221-3p, hsa-miR-17-5, hsa-miR-27a-3, and hsa-miR-25-3p), and 10 mRNAs (GALC, ETNK1, RNF4, SOX4, ZBTB18, SPRY2, RUNX1, MYLIP, BTG2, and MAP2K4) were identified as hub molecules. Conclusions: Thirty plasma exosomal miRNA markers associated with endometriosis were identified and reported. The miRNAs were associated with the promotion of proliferation in mesenchymal cells, as well as the tumor necrosis factor (TNF) and Toll-like receptor signaling pathways, and the differentiation of T helper 1 (Th1) and Th2 cells. These biological processes and pathways could potentially play a significant role in the pathogenesis and progression of EM. The potential clinical value of these miRNAs indicates potential targets for diagnosing and treating endometriosis while also offering new insights into the molecular mechanisms of the disease.